Innovative Nanotechnology a Boon for Fight Against Pandemic COVID–19 - Shehu, Ibrahim Aminu; Auwal, Nura Mustapha; Musa, Muhammad Kabir; Mukhtar, Abubakar; Yusuf, Mashahudu Sha’arani; Yau, Anees Ashir; Muhammad, Murtala; Baba Dala, Yusuf; Sani, Salisu Abdullahi; Ahmad, Mahmoud Seed; Islam, Mojahidul (Frontiers in Nanotechnology, 2021)
COVID – 19 is a contagious disease caused by severe acute respiratory syndrome (SARS-CoV2). The rate at which COVID – 19-virus spread from epidemic to pandemic within a short period is quite alarming. As of July 2020, the Dashboard of the World Health Organization (WHO) recorded over 15 million COVID – 19 cases across 213 countries, with mortality of over 620,000. The governments and healthcare agencies responsible for mitigating the virus's spread have adopted several strategies to end the pandemic. However, all hands were on deck to establish the standard treatment modalities of SARS-CoV-2 through inventing new drugs, vaccine candidates, or repurposing the existing medicines and robust diagnostic tools, in addition to other technological innovations. Therefore, nanotechnology’s employment would play a vital role in bringing multidisciplinary ways of developing affordable, reliable, and powerful tools for diagnosis, in addition to personal protection and effective medicines. Additionally, nanosensors' application would significantly aid the diagnoses of the COVID–19 even on asymptomatic patients, and thus would be an essential means for determining its prevalence. Likewise, nanoscale fibers can optimize personal equipment protection and allow their reusability for medical and economic benefits. Accordingly, the literature was intensively reviewed by searching for the combinations of the research keywords in the official scientific databases such as Science Direct, PubMed, and Google Scholar. Hence, this research highlighted the perspective contributions of nanotechnology in the war against the COVID-19 pandemic.